Le décloisonnement des services financiers - Dumont, Monique (Assurances, 1984)
The Province of Quebec has just passed a law which removes some of the barriers between financial institutions. Larger capital reserves will be required and strictly audited according to procedures now being finalized by the Quebec Government before allowing the institutions concerned to increase the scope and diversity of their business.